The generalized Stackelberg equilibrium of the all-pay auction with complete information - Kai A. Konrad; Wolfgang Leininger (Universität Dortmund, Wirtschafts- und Sozialwissenschaftliche Fakultät, 2006)
In the equilibrium of the all-pay auction with two groups of individual players who move sequentially, only the player with the lowest effort cost has a positive payoff. This payoff and the overall dissipation crucially depend on group composition.
Keywords: D72; D74; 330; Sequential all-pay auction; complete information; generalized cost; generalized Stackelberg game